Consumer Experience and Omnichannel Behavior in Various Sales Atmospheres - Paz, María Dolores Reina; Delgado, Fernando Jiménez (Frontiers in Psychology, 2020)
The conceptual framework for our analysis is the approach to environmental psychology first introduced by the authors Mehrabian and Russell in 1974. Subsequently in 1982 Donovan and Rossiter applied the concept to retail outlets so as to better understand the effect on consumers of atmospheric stimuli experienced in a physical store. Following the developing trend from traditional marketing to new online sales channels, various authors have sought to transfer and validate these theories with virtual outlets or e-stores, so as to validate them in a context of e-commerce. Our study thoroughly analyses and reviews the most widely accepted models in the study of the influence of sales atmospherics on consumer behaviour in physical store environments, and the adaptation and application of such models to today’s omnichannel shopper behaviour, where shopping environments combine physical sales settings with new digital sales atmospheres.